PENGEMBANGAN MEDIA PEMBELAJARAN BERBANTU APLIKASI POWTOON DISERTAI NILAI-NILAI ISLAM PADA MATERI SEGIEMPAT DAN SEGITIGA - Muhammad Faiz Syamil; Ira Vahlia; Satrio Wicaksono Sudarman (EMTEKA: Jurnal Pendidikan Matematika, 2024)
This study aims to develop media in the form of learning videos assisted by the powtoon application accompanied by Islamic values in quadrilateral and triangular material at SMP Negeri 2 Marga Tiga and aims to produce valid and practical learning videos. The model used in this development is the ADDIE model with stages namely Analysis, Design, Development, Implementation, Evaluation. Analysis is to find information, Design is to design learning videos, Development is to produce a product, at the Implementation stage it is not carried out because research is focused on producing products that are valid and practical, Evaluation is for improvement at each stage. The data collection instruments used were interview sheets, validation questionnaires by experts, and student response questionnaires. The validity of the product that has been developed is seen from the results of the validation of material experts obtaining a final assessment with an average percentage of 74% valid category. The validation results by media experts obtained a final assessment with an average percentage of 75.5% valid category. The results of the validation of Islamic values obtained a percentage of 75.5% in the valid category. The product practicality test was carried out by 10 students at SMP Negeri 2 Marga Tiga and obtained a final assessment with an average percentage of 89.5% in the very practical category. From the results of this assessment, it can be concluded that the product developed meets valid and practical criteria.